Metagenomic Analysis Shows the Presence of Bacteria Related to Free-Living Forms of Sulfur-Oxidizing Chemolithoautotrophic Symbionts in the Rhizosphere of the Seagrass Zostera marina - Cúcio, Catarina; Overmars, Lex; Engelen, Aschwin H.; Muyzer, Gerard (Frontiers in Marine Science, 2018)
Seagrasses play an important role as ecosystem engineers; they provide shelter to many animals and improve water quality by filtering out nutrients and by controlling pathogens. Moreover, their rhizosphere promotes a myriad of microbial interactions and processes, which are dominated by microorganisms involved in the sulfur cycle. This study provides a detailed insight into the metabolic sulfur pathways in the rhizobiome of the seagrass Zostera marina, a dominant seagrass species across the temperate northern hemisphere. Shotgun metagenomic sequencing revealed the relative dominance of Gamma- and Deltaproteobacteria, and comparative analysis of sulfur genes identified a higher abundance of genes related to sulfur oxidation than sulfate reduction. We retrieved four high-quality draft genomes that are closely related to the gill symbiont of the clam Solemya velum, which suggests the presence of putative free-living forms of symbiotic bacteria. These are potentially highly versatile chemolithoautotrophic bacteria, able to alternate their metabolism between parallel pathways of sulfide oxidation (via sqr and fcc), nitrate reduction (denitrification or DNRA) and carbon fixation (via CBB or TCA cycle), depending on the environmental availability of sulfide. Our results support the hypothesis that seagrass meadows might function as a source of symbionts for invertebrates that inhabit within or around seagrass meadows. While providing ideal conditions for the proliferation of these free-living forms of symbionts, seagrasses would benefit from their genetic versatility, which contributes to sulfide detoxification and ammonium production, the seagrasses' preferred nitrogen source.